Performance of a combined system of biotrickling filter and photocatalytic reactor in treating waste gases from a paint-manufacturing plant. Issue 2 (17th January 2016) - Zeng, Peiyuan; Li, Jianjun; Liao, Dongqi; Tu, Xiang; Xu, Meiying; Sun, Guoping
Abstract : A pilot-scale biotrickling filter (BTF) was established in treating the waste gases that are intermittently produced from an automobile paint-manufacturing workshop. Results showed that the BTF required longer time to adapt to the aromatic compounds. The removal efficiencies (REs) for all aliphatic compounds reached more than 95% on day 80. Aromatic compounds were not easily removed by the BTF. The REs obtained by the BTF for toluene, ethylbenzene, m -xylene, o -xylene and p -xylene on day 80 were 72.7%, 77.2%, 71.9%, 74.8% and 60.0%, respectively. A maximum elimination capacity (EC) of 13.8 g-C m −3 h −1 of the BTF was achieved at an inlet loading rate of 19.4 g-C m −3 h −1 with an RE of 72%. Glucose addition promoted the biomass accumulation despite the fact that temporal decrease of REs for aromatic compounds occurred. When the inlet loading rates exceed 11.1 g-C m −3 h −1, the REs of the aromatic compounds decreased by 10% to 15%. This negative effect of shock loads on the performance of the BTF can be attenuated by the pre-treatment of the photocatalytic reactor. Nearly all components were removed by the combined system with REs of 99%.